(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A study was carried out for three consecutive seasons (2005/06, 2006/07 and 2007/08) under rain- fed condition, to investigate the effectof some tillage systems on surface runoff and soil erosion in northernGedarif. The study was conducted at the pilot farm of the Faculty ofAgricultural Sciences and Environment, University of Gedarif ,in thenorthern area of Gedarif State ( Latitude 12° 45′ N, Longitude 35° 15′ Eand 540 m above sea level ). The experimental design was randomizedcomplete block with three replications. Treatment were three tillagesystems: No tillage or zero tillage (ZT), offset disc as post harvest tillage(PHT) and wide level disc, farmers practices as control ( WLD ). Raingauge was used to measure the rainfall, whilst the surface runoff and soillosses were measured using runoff plot technique. Total recorded annualrainfall was 368.1mm (2005), 463.6 mm (2006) and 495.2 mm (2007)which was spread over 32, 30 and 32 rainy days during the first , secondand third growing seasons, respectively. The results showed that thesecond season had the best distribution and satisfaction pattern. Itrecorded 15 %, 36 %, 26 % and 5 % for July, August, September andOctober, respectively, compared to 24 % ,53 % 13 % and 2 % ; and 29% ,41 % , 21 % and 1 % for first and third seasons in the same months.Zero tillage treatment showed more runoff and soil loss than PHT andWLD. In terms of accumulation, ZT produced more runoff by 28 % and 9% and soil loss by 53 % and 28 % over PHT and WLD respectively forfirst season ,30 % and 13 % runoff and 28 % and 13 % soil loss for thesecond season and 55 % and 23 % runoff and 105 % and 24 % soil lossfor third season . The post harvest tillage reduced average annual runoffand soil loss to the lowest values compared to the Wide level disk andZ T.